Transplantation of Stem Cells from Human Exfoliated Deciduous Teeth Decreases Cognitive Impairment from Chronic Cerebral Ischemia by Reducing Neuronal Apoptosis in Rats - Shu Zhu; Dongyu Min; Jianhong Zeng; Yetao Ju; Yao Liu; Xu Chen (Stem Cells International)
Stem cells from human exfoliated deciduous teeth (SHED) are a unique postnatal stem cell population with high self-renewal ability that originates from the cranial neural crest. Since SHED are homologous to the central nervous system, they possess superior capacity to differentiate into neural cells. However, whether and how SHED ameliorate degenerative central nervous disease are unclear. Chronic cerebral ischemia (CCI) is a kind of neurological disease caused by long-term cerebral circulation insufficiency and is characterized by progressive cognitive and behavioral deterioration. In this study, we showed that either systemic transplantation of SHED or SHED infusion into the hippocampus ameliorated cognitive impairment of CCI rats in four weeks after SHED treatment by rescuing the number of neurons in the hippocampus area. Mechanistically, SHED transplantation decreased the apoptosis of neuronal cells in the hippocampus area of CCI rats through downregulation of cleaved caspase-3. In summary, SHED transplantation protected the neuronal function and reduced neuronal apoptosis, resulting in amelioration of cognitive impairment from CCI. Our findings suggest that SHED are a promising stem cell source for cell therapy of neurological diseases in the clinic.